A kinematic analysis of rugby lineout throwing - Trewartha, T.; Casanova, R.; Wilson, C. (Journal of Sports Sciences, 2008)
To characterize rugby union lineout throwing technique, three experienced male rugby players performed throwing trials under varying conditions of distance and trajectory. Motion analysis permitted the recovery of joint centre coordinates at 120 Hz and the construction of a three-dimensional linked segment model for calculation of joint angle and centre of mass time histories. All participants exhibited greater accuracy at shorter throwing distances, although the accuracy decrement was less in players of higher standard. Participants demonstrated different alterations in technique when performing throws of longer distances, either showing increased magnitudes of upper-body joint angle velocities (less accurate thrower) or lower-body joint velocities (more accurate thrower). The most elite thrower exhibited greater consistency in timing of peak joint angle velocities, with an overall standard deviation of 0.008 s compared with 0.027 s for the least accurate thrower. Data from participants of lesser ability suggest that changes are made to both magnitudes and timing of joint kinematics, which leads to increased variability in performance. The implications for players and coaches include the need to develop core strength to permit limited changes to the timing and magnitude of upper-body joint actions while allowing sufficient end-point velocity to be imparted on the ball.